Preparation and characterization of potato starch microparticles with acrylamide by microwave radiation - Rodríguez Pineda, Lina María; Muñoz Prieto, Efren de Jesús; Rius Alonso, Carlos Antonio; Palacios Alquisira, Joaquín (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 149-159).